Differential Responses of Tobacco to the Citrus Variegated Chlorosis and Coffee Stem Atrophy Strains of Xylella fastidiosa - Lopes, Silvio A. [UNESP]; Raiol-Junion, Laudecir L. [UNESP]; Torres, Simone C. Z.; Martins, Elaine C.; Prado, Simone S.; Beriam, Luis O. S. (Amer Phytopathological Soc, 2020)
Xylella fastidiosa comprises a diverse group of xylem-limited, insect-transmitted bacterial pathogens. In Brazil, the citrus variegated chlorosis (CVC) and coffee stem atrophy (CSA) diseases are caused by X. fastidiosa subspecies pauca transmitted by common insect vectors. No simple protocol allowing strain discrimination exists, making epidemiological studies, which are important for devising control measures, difficult to undertake. Here, we show that both strains can easily be distinguished based on the pattern of leaf symptoms that they induce on pin prick-inoculated tobacco seedlings, namely small orange lesions and large necrotic lesions induced by the CVC and CSA strains, respectively. These differential responses allowed us to investigate whether mixed strain infections would occur in citrus or coffee trees in the field. Seedlings were individually inoculated with X. fastidiosa colonies recovered from citrus or coffee plants from various locations at three different times. No mixed infections were detected. In two experiments, the citrus and coffee strains infected only their original hosts as well as tobacco. The usefulness of this tobacco bioassay as a tool to study X. fastidiosa spread was demonstrated. It provided evidence that, over the years, the CVC and CSA pathogens have remained limited to their original hosts, despite crop proximity and the presence of sharpshooter vectors that favor transmission of the bacteria to and between both host species.
Keywords: bacteriology; disease management; epidemiology; etiology; inoculum sources; population biology